Portable indocyanine green perfusion assessment: An adjunct to visual assessment in burn wound healing in second-degree burns - Pradeoth Mukundan Korambayil; Prashanth Varkey Ambookan; Rameela Ravindran Karangath (Wolters Kluwer Medknow Publications, 2019)
Aim: To identify perfusion differences between the areas of different depths and to evaluate the potential of portable indocyanine green (ICG) perfusion assessment to determine the likelihood of healing in burns compared with visual assessment. Materials and Methods: This interventional study was carried out at the burn unit and plastic surgery department, from April 2017 to September 2017. A total of 20 patients with superficial and partial thickness burns <15% for whom the burn assessment was done with portable ICG perfusion assessment and visual assessment were included in the study. The results regarding the excision of burn wound and burn wound healing were compared. Results: Of 20 patients, 14 patients did not have any discrepancy with the clinical findings and ICG perfusion assessment. The findings of five patients appeared clinically deep, but perfusion was present which did not require surgical intervention. One patient had patchy perfusion and finally required surgical correction. Conclusion: ICG perfusion assessment appeared to be effective in preventing surgical intervention in patients by differentiating deep to superficial second-degree burns. Proper clinical assessment and ICG perfusion assessment as an adjunct can improve the outcome of burn wound.